The last fifteen years of stagnation in Italy: A Business Cycle Accounting Perspective - Renzo Orsi; Francesco Turino (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2010)
In this paper, we investigate possible sources of declining economic growth performance in Italy starting around the middle of the '90s. A long-run data analysis suggests that the poor performance of the Italian economy cannot be ascribed to an unfortunate business cycle contingency. The rest of the euro area countries have shown better performance, and the macroeconomic data show that the Italian economy has not grown as rapidly as these other European economies. We investigate the sources of economic fluctuations in Italy by applying the Business Cycle Accounting procedure introduced by Chari, Kehoe and McGrattan (2007). We analyze the relative importance of efficiency, labor, investment and government wedges for business cycles in Italy over the 1982-2008 period. We find that different wedges have played different roles during the period, but the efficiency wedge is revealed to be the main factor responsible for the stagnation phase beginning around 1995. Our findings also show that the improvement in labor market distortions that occurred in Italy during the '90s provided an alleviating effect, preventing an even stronger slowdown in per capita output growth.
Keywords: E65; O41; O52; 330